Socioeconomic position and overweight among adolescents: data from birth cohort studies in Brazil and the UK - Menezes Ana; Barros Fernando C; Golding Jean; Victora Cesar G; Matijasevich Alicia; Araujo Cora L; Smith George (BMC, 2009)
Abstract Background Developed and developing countries are facing rapid increases in overweight and obesity among children and adolescents. The patterns of overweight/obesity differ by age, sex, rural or urban residence and socioeconomic position (SEP) and vary between and within countries. Methods We investigated patterns of SEP - overweight status association among adolescents from the UK (ALSPAC) and Brazil (the 1982 and 1993 Pelotas birth cohort studies). All analyses were performed separately for males and females. Logistic regression analysis was used to examine the relationships between overweight status and two SEP indicators - family income and maternal education. Results A strong positive association was observed in 11-year-old boys from the 1993 Pelotas cohort, with higher prevalence of overweight among the least poor and among those whose mothers had more years of schooling (x2 for linear trend p < 0.001). In ALSPAC study higher prevalence of overweight was seen among boys whose mothers had lower educational achievement (x2 for linear trend p = 0.006). Among 11 year-old girls from 1993 Pelotas cohort study there was a positive association (higher prevalence of overweight in the higher socioeconomic and educational strata, x2 for linear trend p < 0.001 and p = 0.01, respectively) while an inverse association was found in the ALSPAC study (x2 for linear trend p < 0.001). Among males from the 1982 cohort study, overweight at 18 years of age showed a positive association with both SEP indicators while among females, the reverse association was found. Conclusion The results of this study demonstrate that the social patterning of overweight varies between and within populations over time. Specific approaches should be developed within populations in order to contain the obesity epidemic and reduce disparities.